PERPPU NOMOR 1 TAHUN 2017 TENTANG “AKSES INFORMASI KEUANGAN UNTUK KEPENTINGAN PERPAJAKAN” DAN IMPLIKASINYA TERHADAP LEMBAGA KEUANGAN DI INDONESIA - Kusworini Kusworini (JURNAL ILMIAH HUKUM DAN DINAMIKA MASYARAKAT, 2017)
Access of tax officers to the financial industry customers is set forth in Perppu No. 1 2017Th, the issuance of this rule is closely linked to the financial information exchange agreement between the Automatic Exchange of Financial Account Informce (AEoFIA) organized by Member States of the Organization for Economic  Co-operation and Development (OECD), including Indonesia. At the same time the Perppu is at the same time the capital of the tax authorities to pursue the tax target. The tax authorities are authorized to request additional information and evidence from financial institutions, as the latter annuls several articles which have been the secret locking of financial industry customers. This Perppu will raise tax revenues given the low acceptance of the current tax base. Nevertheless this Perppu would be perfect if it could be metamorphosed into Law.